LINIERISASI ITERATIF PADA METODE BEDA HINGGA UNTUK MEYELESAIKAN MASALAH KONDISI BATAS DIRICHLET PERSAMAN DIFERENSIAL BIASA NON LINIER - Sitompul, Hery Andi; W.B.Siahaan, Enzo; Simamora, Antonius; Gultom, Togar Timoteus; A, Arfis; Mulia, Mulia (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2025)
Dirichlet boundary condition problems in nonlinear ordinary differential equations generally have to be worked out numerically by applying the concept of finite differences, producing a system of non-linear equations. The Newton and Broyden methods are very popular for solving a system of non-linear equations, but both require very long calculation times if the variables are on a large scale. The concept of iterative linearization of a system of non-linear equations produced by the finite difference method in a nonlinear differential equation, it will provide new insight into the problem of Dirichlet boundary conditions.